Evaluation of parent and youth experiences in advisory groups as part of a mental healthcare clinical trial: protocol for a mixed-method study - Maria-Jose Santana; Gina Dimitropoulos; Suneeta Monga; Isabelle J Gagnon; Bruce Wright; Jananee Rasiah; Katrina Hurley; Antonia Stang; Amanda Newton; Stephen Freedman; Jennifer Thull-Freedman; Kassi Prisnie; et al. (BMJ Open)
Introduction Patient engagement in healthcare research is a necessity to ensure that research objectives align with priorities, outcomes and needs of the population under study, and to facilitate ease of implementation and adoption of findings. In clinical trials, there is an increasing focus on patient engagement during the planning and conduct of clinical trials due to the potential for ethical and methodological benefits. As patient engagement in clinical trials increases, there is a need to evaluate the approaches of these activities to contribute evidence on what is most appropriate and successful. The purpose of this study is to evaluate patient engagement processes and the activities of patient partners during and after a paediatric mental healthcare trial.Methods and analysis Using a mixed-methods study design, we will evaluate patient partners’ engagement activities across set time-points during the trial and after trial completion. In this study, the term ‘patient partner’ is inclusive of two groups of people with lived experience: (1) caregivers (parents, formal/informal caregivers and family), and (2) youth (aged 15–24 years). Engagement will be evaluated using the participant and project questionnaires of the Public and Patient Engagement Evaluation Tool (PPEET), followed sequentially by semi-structured interviews. Quantitative data from the PPEET questionnaire will be analysed and reported using descriptive statistics. Data from open-ended questions from the PPEET questionnaires and semi-structured interviews will be analysed using thematic analysis.Ethics and dissemination Approval from Athabasca University Research Ethics Board will be obtained for this project. Findings will be disseminated at both academic and public venues whether in-person or online, and using platforms that are caregiver and youth friendly.Trial registration number NCT04902391.